A GIS-based Spatial Multi-criteria Approach for Flash Flood Risk Assessment in the Ngan Sau-Ngan Pho Mountainous River Basin, North Central of Vietnam: DOI: 10.32526/ennrj.18.2.2020.11 - Dai Hoang, Van; Thai Tran, Hong; Tien Nguyen, Thanh (Environment and Natural Resources Journal, 2019)
Flash flood risks in the Ngan Sau-Ngan Pho mountainous river basin (north central of Vietnam) were examined based on GIS and a spatial multi-criteria approach. A set of indicators were firstly proposed for the assessment of hazard, exposure and vulnerability. Analytic hierarchy process (AHP) technique and Iyengar and Sudarshan’s method were then applied for calculating weights of hazard and vulnerability indicators, respectively. Flash flood risks were assessed by means of the “risk triangle” approach and were finally validated using past flood records. It was found that flash flood hazard was mainly at medium and low levels, with a very high hazard area of 178.6 ha accounting for 0.1% of the total river basin. Exposure at high and very high levels was mainly detected in the economic center of the basin. The high and very high vulnerability areas accounting for 98.2% of the total area were mainly concentrated in mountainous areas. The largest area was low risk totaling 219,083.1 ha (accounting for 68.6% of the basin area), followed by 67,148.6 ha (very low risk: 21%), 27,181 ha (medium risk: 9%), 5,909.7 ha (high and very high risks: 1.8%). These results demonstrate the proposed set of indicators, GIS and spatial multi-criteria analysis allow for effective flash flood risk assessment in mountains.